Preparation and Synthetic Application of Highly Reactive 6-Trifluoromethanesulfonyloxylllmazine; A Novel Method for 6-Substituted Lumazines - Murata Shizuaki; Sugimoto Takashi; Murakami Katsuhiko (Pteridines, 1997)
1,3-Dimethyl-6-trifluoromethanesulfonyloxylumazine is prepared by a reaction of 1,3-dimethyllumazine 5-oxide with trifluoromethanesulfonic anhydride and is converted efficiently into lumazines with various substituents, for example amino, halogens, phenylthio, thiocyano, phenylseleno, and so on, on the 6-position by reactions with the corresponding nucleophiles.